Increased Stability in Carbon Isotope Records Reflects Emerging Complexity of the Biosphere - Schobben, Martin; van de Schootbrugge, Bas (Frontiers in Earth Science, 2019)
Preference for certain stable isotopes (isotope fractionation) during enzyme-mediated reactions is a universal aspect of life. For instance, carbon isotopes are fractionated during anabolic (e.g., photosynthate production) and catabolic (e.g., methanogenesis) reactions. These biological processes exert a major control on ambient micro-scale chemical conditions as well as the large-scale exogenic carbon reservoir. Combined with the ubiquity of bio-mediated carbonate mineral nucleation and obligate enzymatic skeletonization, these biochemical reactions and their control on the exogenic carbon pool are known to leave distinct imprints on carbonate minerals which accumulate as sediments throughout Earth’s history. Here, we study the evolution of the marine carbonate-carbon isotope record based on database compilations from the Precambrian and the Phanerozoic. By looking at the frequency distribution of the amplitude of stratigraphic variation at various temporal resolutions, we assess trends in the carbonate-carbon isotope variability. Part of this variation can only be explained by authigenic and diagenetic carbonate mineral additions, which carry metabolic carbon isotope signatures created in the vicinity of cells and secluded (sub-)seafloor micro-environments. It can be envisioned that compartmentalization (membrane enclosed regions), the accumulation of extracellular polymeric substances (biofilms), and restricted fluid exchange in the early diagenetic environment can create sharp isotope gradients that lead to a high-order of micro-scale carbon isotope variability being imprinted in carbonate rock. The frequency of the high-amplitude variation diminishes with the development of more complex life (metazoan-dominated biosphere); presumably through the dispersing action of bioturbation (eradicating these micro-environments), increased grazing pressure and the advent of obligate biomineralization. On the other hand, stark chemical gradients in a world dominated by unicellular life (prokaryotes and to a lesser extent eukaryotes) are thought to leave a distinctly more variable C isotope signature in carbonate rock. An enhanced understanding of the biogenicity of carbonate carbon isotope signatures at multiple spatial and temporal scales provides a baseline that is usable in the search for signs of (past) extraterrestrial life.